Cardiac manifestation is evident in chorea-acanthocytosis but different from McLeod syndrome. (July 2021) - Quick, Silvio; Heidrich, Felix Matthias; Winkler, Max-Valentin; Winkler, Anna Helene; Ibrahim, Karim; Linke, Axel; Speiser, Uwe; Grabmaier, Ulrich; Buhmann, Carsten; Marxreiter, Franz; Saft, Carsten; Danek, Adrian; et al.
Abstract: Introduction: We aimed to study the various cardiac manifestations of the two core neuroacanthocytosis (NA) syndromes, namely chorea-acanthocytosis (ChAc) and McLeod syndrome (MLS). So far, cardiac involvement has been described as specific feature only for MLS. Methods: We studied six patients with ChAc (mean age 44.5 years, five men, one woman) and six patients with MLS (mean age 57.1 years, all men). Cardiac evaluation included echocardiography and/or cardiac magnetic resonance imaging (cardiac MRI), 24-h ECG-recording and examination of cardiac biomarkers. Results: Cardiac involvement of ChAc was found in four of six patients. Two patients showed mildly reduced left ventricular ejection fraction (LVEF), two other patients mild to moderate left ventricular (LV) dilatation. Neither an increase in ventricular ectopic beats nor ventricular tachycardia were evident in ChAc. Four of five MLS patients showed left ventricle dilatation and reduced left ventricular ejection fraction (LVEF). Two of these, in addition, had critical ventricular tachycardia. High sensitive troponin T was elevated in all patients, for whom data were available (n = 10). In contrast, elevation of high sensitive troponin I was found in one of six ChAc and one of two MLS patients. Conclusion: For the first time, we reveal cardiac involvement in a cohort of six ChAc patients, while the risk to develop heart failure seems lower than in MLS. Our study confirms the malignant nature of MLS in terms of ventricular arrhythmias and progression to advanced heart failure. Herein, we define disease-specific recommendations for cardiac assessment in both conditions. Highlights: This is an investigation of cardiac manifestation in neuroacanthocytosis syndromes. For the first time, we clearly reveal cardiac manifestation of chorea acanthocytosis. We confirm the malignant nature of McLeod syndrome regarding cardiac manifestation. We define disease-specific recommendations for cardiac assessments.